2020
DOI: 10.1123/jsr.2019-0428
|View full text |Cite
|
Sign up to set email alerts
|

Near Point of Convergence Deficits and Treatment Following Concussion: A Systematic Review

Abstract: Context: Convergence dysfunction following concussion is common. Near point of convergence (NPC) is a quick and easy assessment that may detect oculomotor dysfunction such as convergence insufficiency (CI), but NPC measurements are rarely reported. Convergence dysfunction is treatable in otherwise healthy patients; the effectiveness of oculomotor therapy following concussion is unclear. Objectives: The purpose of this article was to systematically review the literature and answer the following clinical questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Oculomotor abnormalities such as poorer depth perception, poorer baseline visual acuity, longer near point convergence distance were moderately correlated with poorer functional mobility. Visual deficits have been studied extensively after traumatic brain injury (45,(60)(61)(62)(63)(64)(65)(66), and in combination with vestibular dysfunction have been shown to affect balance (21). Kleffelgaard et al examined 65 individuals (mean age 39.2 ± 12.9 years) who were 3 months post-injury and reported that 78% had poorer high-level balance while 77% had lower scores on high level mobility tasks compared to normative values.…”
Section: Discussionmentioning
confidence: 99%
“…Oculomotor abnormalities such as poorer depth perception, poorer baseline visual acuity, longer near point convergence distance were moderately correlated with poorer functional mobility. Visual deficits have been studied extensively after traumatic brain injury (45,(60)(61)(62)(63)(64)(65)(66), and in combination with vestibular dysfunction have been shown to affect balance (21). Kleffelgaard et al examined 65 individuals (mean age 39.2 ± 12.9 years) who were 3 months post-injury and reported that 78% had poorer high-level balance while 77% had lower scores on high level mobility tasks compared to normative values.…”
Section: Discussionmentioning
confidence: 99%
“…Several oculomotor measures have been investigated for use as potential biomarkers of altered brain function after TBI, including metrics of fixation, smooth pursuit, saccades, 100 and convergence. 101 One study demonstrated that oculomotor assessment may be an indicator of decreased integrity of frontal white matter tracts and of altered attention and working memory functioning. 102 Moreover, researchers have developed mobile eye-tracking devices, which could benefit future clinical research by capturing eye movements remotely.…”
Section: Diagnostic Biomarkersmentioning
confidence: 99%
“…The closest point at which both eyes can converge inward at the same time is called the near-point-of-convergence (npc) [12,13]. When the npc moves away from the eye, objects appear blurry when performing near work, such as convergence and accommodation insufficiency, and subjective symptoms, such as ophthalmocopia occur.…”
Section: Npc Examinationmentioning
confidence: 99%